Bankruptcy in international vs domestic markets: Evidence from the airline industry. (February 2020) - Bock, Sebastian; Mantin, Benny; Niemeier, Hans-Martin; Forsyth, Peter John
Abstract: We study the effects of Chapter 11 bankruptcy protection on competitive product pricing in both domestic and international markets using data from the airline industry. We find a decline of about 5% in domestic markets and an even more significant drop in international markets. Further, in international markets the competing carriers respond by dropping their prices as well, whereas they slightly increase them domestically. By contrast, existing literature considers only domestic markets finding a more moderate fare drop of about 3% in domestic markets by the bankrupt carrier, with mixed results on the fare drop by competitors.